Larval shell chemistry of the Olympia oyster (Ostrea lurida) in Puget Sound, WA to assess population connectivity and restoration planning - Megan Hintz; Bonnie J. Becker; Henry S. Carson; Verena H. Wang; Marco B. A. Hatch; Brian Allen; Brian Rusk (PLoS ONE, 2025)
The Olympia oyster (Ostrea lurida) is the only native oyster species along the west coast of North America and is culturally and ecologically important. However, Olympia oyster populations have been severely depleted, prompting ongoing restoration efforts in Puget Sound, WA, and beyond. Understanding population connectivity is vital for successful restoration planning to ensure resilience and genetic diversity. This study examined the potential for using trace elemental “fingerprints” in Olympia oyster shells to track larval dispersal and connectivity at regional scales within Puget Sound. Brooded larvae were collected via non-lethal sampling at eight sites grouped into three geographic regions. Shell chemistry analysis showed the ability to distinguish these regions from each other with approximately 75% accuracy, demonstrating feasibility for addressing connectivity questions among sub-basins. Additionally, regional signatures were found to be temporally stable within one reproductive season, facilitating annual sampling regimes. Although settlers of unknown origin collected at two restoration sites could not yet be confidently assigned to specific source regions, nor could they be divided into groups in a cluster analysis, likely due to methodological constraints, this study provides a proof of concept and foundation for further developing this technique. With targeted improvements to analytical methods for microscopic larval shells, shell elemental fingerprinting shows promise to greatly inform ongoing restoration efforts by elucidating population connectivity patterns for this culturally and ecologically important native oyster species at ecologically relevant scales.